Implementation of mMINDS monitoring for alcohol withdrawal at an inpatient academic psychiatric facility - Leah A. Surbaugh, PharmD, BCPP; Taylor Kelsey, PharmD, BCPP; Brittany L. Melton, PharmD, PhD; Karen E. Moeller, PharmD, BCPP (Mental Health Clinician)
Introduction Patients who abruptly stop the consumption of alcohol are at risk of alcohol withdrawal syndrome (AWS). Guidelines recommend the use of a validated clinical withdrawal scoring tool to assess the severity of a patient’s withdrawal. The modified Minnesota Detoxification Scale (mMINDS) provides detailed definitions to help guide nurses in objectively scoring patients’ withdrawal symptoms. Although mMINDS has been validated in a medical intensive care unit, it has not yet been validated in a psychiatric facility. Methods The primary objective was to determine if using mMINDS was preferred by nurses and increased confidence in assessing AWS compared with the current standard of care in an adult inpatient psychiatric hospital. After 3 months of using mMINDS, nurses were asked to complete a survey to assess their preference and confidence with mMINDS. A retrospective review was also conducted on all patients, 18 years and older, who were monitored for AWS both pre- and post-implementation of mMINDS. Results Overall, 60% (n = 12) of nurses selected mMINDS as the scoring tool they felt most confident with assessing AWS. Patients in the mMINDS group also received lower cumulative doses of benzodiazepines, although this finding did not reach statistical significance (0.75 mg post-implementation vs. 1.75 mg pre-implementation [P = 0.101]). Discussion The use of mMINDS was preferred by nurses for monitoring AWS in patients hospitalized at an inpatient psychiatric hospital. These results suggest that mMINDS may be an effective tool for monitoring AWS in an inpatient psychiatric setting.